Navigating Limited and Uncertain Access to Subsidized Housing After Prison - Keene, Danya E. (Hous Policy Debate, 2017)
An emerging literature has documented the challenges that formerly incarcerated individuals face in securing stable housing. Given the increasingly unaffordable rental market, rental subsidies represent an important and understudied source of stable housing for this population. The existing literature has described substantial discretion and a varied policy landscape that determine former prisoners’ access to housing subsidies, or subsidized housing spaces that are leased to members of their social and family networks. Less is known about how former prisoners themselves interpret and navigate this limited and uncertain access to subsidized housing. Drawing on data from repeated qualitative interviews with 44 former prisoners, we describe the creative and often labor-intensive strategies that participants employed to navigate discretion and better position themselves for subsidized housing that was in high demand, but also largely out of reach. Our findings also illustrate the potential costs associated with these strategies for both participants and members of their social and family networks.